MARKETING ORIENTATION OF FAMILY BUSINESSES - Kyurova, Vyara (Revista Inclusiones, 2019)
This article presents the results of a survey of marketing orientation of family businesses in Bulgaria. The aim is to outline the specific features of the marketing orientation of family business and present its main problems. The assessment of the marketing orientation is based on the results of personally organized survey among 86 representatives of family businesses in three major sectors of activity – manufacture, trade and services – in Bulgaria. It also discusses the theoretical aspects of marketing orientation and its components. Based on the results of the survey are formulated the main problems of the marketing orientation of family business in Bulgaria.